Combined Foot Care and Motivational Interviewing in Preventing Diabetic Foot Ulcers - Vina Vitniawati; Tuti Suprapti (Sarana Ilmu Indonesia (salnesia), 2026)
Type II diabetes mellitus is a chronic metabolic disease with increasing prevalence and a high risk of Diabetic Foot Ulcers, leading to morbidity, amputation, and reduced quality of life. Prevention requires proper foot care and continuous education, yet low patient knowledge and motivation remain major barriers. Motivational Interviewing may improve patient motivation and adherence to self-care. This study aimed to evaluate the effectiveness of combining foot care education and Motivational Interviewing in patients with type II diabetes mellitus. A quasi-experimental pretest-posttest design without a control group was conducted among 15 participants of the Chronic Disease Management Program at Riung Bandung Community Health Center for three months. Interventions included face-to-face education, foot care practice, and motivational counseling. Outcomes were assessed using Diabetic Foot Ulcer risk scores, knowledge, and adherence instruments. The results demonstrated a significant improvement in patient knowledge, but no significant changes in adherence or Diabetic Foot Ulcer risk. The intervention enhanced patients’ understanding of diabetes complication prevention; however, behavioral and clinical outcomes remained unchanged. Future studies should apply longer interventions, involve family support, and include larger samples with control groups.